2022
DOI: 10.1038/s41598-022-08531-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution for circular tunnel excavated in strain-softening rock masses considering damaged zone

Abstract: Despite the extensive investigation on the stress and displacement distributions in tunnels, few have considered the influences of the damaged zone around a tunnel on the strength and stiffness parameters of the surrounding rock, including the gradual variation in the damaged factor D and dimensionless damaged radius $$\rho^{{\text{d}}}$$ ρ d , under the effect of excavation disturbance. In this paper, a numerical sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The contraction of cavities excavated in strain-softening rock masses has so far been studied using analytical, semi-analytical and numerical methods, which can generally be categorized into two groups based on their treatment of strain within the plastic zone: rigorous methods utilizing incremental plasticity and simplified methods. Recent works and comprehensive reviews of the state of the art can be found in 1 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The contraction of cavities excavated in strain-softening rock masses has so far been studied using analytical, semi-analytical and numerical methods, which can generally be categorized into two groups based on their treatment of strain within the plastic zone: rigorous methods utilizing incremental plasticity and simplified methods. Recent works and comprehensive reviews of the state of the art can be found in 1 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, when using the RS2 (Rocscience) program, when developing an elastic-plastic model taking into account the Coulomb -Mohr criterion with residual strength, data from the passport of the residual strength of rocks are required [23,24]. The frequently used Hook -Brown strength criterion additionally requires workings mapping data to assess the disturbance of the rock mass [25][26][27]. Therefore, the necessary initial data can be obtained only as a result of laboratory tests and field studies.…”
Section: Introductionmentioning
confidence: 99%